Effect of microsegregation and heat treatment on localised γ and γ’ compositions in single crystal Ni-based superalloys - Strutt, VCI; Jenkins, BM; Woolrich, JM; Appleton, M; Moody, MP; Bagot, PAJ (Elsevier, 2023)
The present work investigates the impact of residual segregation on the underlying microstructure of a 3rd generation single crystal, nickel-based superalloy to understand potential variation in mechanical behaviour between dendrite cores and interdendritic regions. Despite the applied heat-treatments, chemical variation between dendrite cores and interdendritic regions persisted particularly for elements Re, Nb and Ta. Atom probe tomography (APT) was utilized for its nanoscale capability to map site-specific chemical changes in the γ matrix, γ’ precipitates and across the γ/γ’ interface. Greater interfacial segregation of Re, matched by a corresponding depletion of Ni were observed within dendrite cores, with the extent found to increase following heat treatment. Differences in lattice parameters between dendrite cores and interdendritic regions were identified, with larger lattice misfits associated with interdendritic regions.